Analysis of The Sentiment of Indonesian Presidential Candidates for 2024 on The YouTube Social Media Platform using The Support Vector Machine Method - Wahyudi, Adhi; Santoso, Gatot Budi; Sholihah, Binti (Penerbitan Universitas Trisakti, 2024)
Indonesia is a country led by a president. The term of office of a president will be democratically elected every five years. The current president will end his term of office in 2024. So that in that year, the people will hold direct general elections to determine the president between 2024 and 2029. Before the general elections are held in Indonesia itself, it is closely related to the campaigns of each presidential candidate carried out by their supporters. Campaigns are usually carried out directly to village locations and social media Twitter/Facebook/YouTube. This study aims to analyze the sentiment of comments on the YouTube platform for three Indonesian presidential candidates, Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto in the context of the 2024 PresidentialElection.. Indonesia is a nation led by a president, with the presidential term lasting five years, determined through democratic elections. The incumbent president's tenure will conclude in 2024. Consequently, during that year, citizens will participate in a direct general election to select the president for the 2024- 2029 period. Prior to the domestic general elections, there is a strong link to the campaigning efforts of each presidential contender, which are conducted by their respective supporters. Campaign activities typically extend to rural areas and popular social media platforms such as Twitter, Facebook, and YouTube. This research aims to assess the sentiment of comments on the YouTube platform regarding three potential Indonesian presidential candidates: Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto. This analysis takes place in the context of the upcoming 2024 Presidential Election.